PENGUJIAN LUCK PRIMING DAN BELIEF IN SUPERSTITIONS DALAM PEMBENTUKAN KESEDIAAN MEMBELI KEMBALI PRODUK SETELAH TERJADI KEGAGALAN PRODUK - Adi Zakaria Afiff; Hetty Karunia Tunjungsari (Jurnal Manajemen., 2013)
This study explain how the use of luck priming in print advertising which occurred in Indonesia recently has an effect on how consumers with believe insuperstition develops their product evaluation, especially when they are experiencing product failure. We expand previous study on the relationship of consumers believe in superstition and product failure by further examining their repurchase intention of the product using 2x2 factorial experimental design. The findings confirmed that luck priming and belief in superstition have significant influence on consumers satisfaction, which shown as greater consumers dissatisfaction on product with luck priming for those with weak belief in superstition. However, our hypotheses in the influence of luck priming and belief in superstition on repurchase intention was also statistically supported. This evidence reinforce previous studies on belief in superstition as a chronic belief which stays in mind of a consumer.